The effect of internet services on child education outcomes: evidence from poa! Internet in Kenya. Issue 1 (2nd January 2022) - Okyere, Charles Yaw
ABSTRACT: In 2016-2018 poa! Internet, a private internet service provider, distributed free internet services across schools in Nairobi, Kenya. Using inverse probability weighting (IPW) method, the study finds that the intervention significantly increases students' internet use and training, receipt of information on educational content, and participation in information and communication technologies (ICTs) education programmes. However, the study does not find evidence that internet services increase school attendance. The results suggest that facilitating access to internet services in schools can significantly increase child computer and internet skills and training in developing countries, even if those investments have limited gains on school attendance.